Pengaruh Layanan Digital Mobile Banking dan Kepuasan Nasabah terhadap Loyalitas Nasabah Bank Syariah Indonesia - Dika Setiagraha; Ilham Prawidi Sakti; Batin, Mail Hilian (ARBITRASE: Journal of Economics and Accounting, 2023)
This study aims to determine digital services in the form of mobile banking services and customer satisfaction and how they impact loyalty for Bank Syariah Indonesia (BSI) customers. The method used uses Partial Least Square (PLS) as a data analysis method in order to find out how far the role of digital mobile banking services can affect customer loyalty. The research sample was obtained from 100 customers of Bank Syariah Indonesia in Palembang city. The results of this study indicate that the mobile banking service variable (X1) has no effect on customer loyalty (Y). On the other hand, in terms of customer satisfaction (X2), its role influences customer loyalty (Y). The customer loyalty variable is 0.693 or 69% which is interpreted to mean that the magnitude of the factors influencing customer loyalty of Bank Syariah Indonesia Palembang can be explained through digital mobile banking services and customer satisfaction. Meanwhile, the remaining 31% can be explained by other factors.